2017
DOI: 10.2139/ssrn.2895546
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Approach to the Use of Critical Thinking Skills in Writing: The Case of Moroccan EFL University Students

Abstract: Training students to think critically is one of the most serious challenges that face Moroccan higher education, with experts being in unanimous agreement that critical thinking should be part of any instructional practice. In actual fact, a number of studies have come to the conclusion that students who have the ability to provide a critical assessment of the knowledge and information they receive-be they inside or outside of the classroom--can become critical thinking individuals, successful professionals, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
1
9
1
Order By: Relevance
“…Though the sample is too small to make generalizations about Moroccan undergraduate EFL learners, this finding is in accord with other studies which measured the CT ability of first-year students majoring in English (Amrous & Nejmaoui, 2016;Pei et al, 2017). In their developmental account of CT in argumentative writing across three different academic levels, Amrous and Nejmaoui (2016) concluded that Moroccan Semester-Two students majoring in English do not make use of sufficient CT skills in argumentative writing. Similarly, the findings shared by Pei et al (2017) indicate that the level of CT skills among Chinese students majoring in English is low.…”
Section: The State Of Affairs Of Ct Skills In Argumentative Writing Among Efl Learnerssupporting
confidence: 80%
See 1 more Smart Citation
“…Though the sample is too small to make generalizations about Moroccan undergraduate EFL learners, this finding is in accord with other studies which measured the CT ability of first-year students majoring in English (Amrous & Nejmaoui, 2016;Pei et al, 2017). In their developmental account of CT in argumentative writing across three different academic levels, Amrous and Nejmaoui (2016) concluded that Moroccan Semester-Two students majoring in English do not make use of sufficient CT skills in argumentative writing. Similarly, the findings shared by Pei et al (2017) indicate that the level of CT skills among Chinese students majoring in English is low.…”
Section: The State Of Affairs Of Ct Skills In Argumentative Writing Among Efl Learnerssupporting
confidence: 80%
“…First, although universities are supposed to be the ideal place where students are trained to think critically about the knowledge they acquire, there are claims that universities fail to instill CT in their students (Halpern, 2014;Pithers and Soden, 1991). The second claim is that previous research on CT among EFL learners points that students majoring in English or a foreign language focus their attention on developing their language proficiency at the expense of developing their reasoning and thinking skills (Amrous and Nejmaoui, 2016;Belghiti, 2012). Given these claims, the present study purports to investigate the potential effect of explicitly integrating CT skills in a course of writing on EFL learners' use of CT skills in argumentative writing.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Like many other nations of the MENA region (Amrous & Nejmaoui, 2016;McLellan, 2009), the literature often reports the limited development of learners' critical thinking skills within Oman. Kumar and James (2015) administered an adapted version of the International Journal of Instruction, January 2020 • Vol.13,No.1 Watson-Glaser Critical Thinking Appraisal (WGCTA) to 281 diploma-level students at Nizwa College of Technology to determine their critical thinking levels, while also examining if statistically significant differences based on gender and department existed.…”
Section: Assessment Of Critical Thinking In Omanmentioning
confidence: 99%
“…Despite the nature of these challenges, there is evidence that an awareness of the importance of developing learners' critical thinking skills is increasing among instructors, students and policymakers in at least some MENA nations (Muasher & Brown, 2018;Tawadrous, 2014), with this often being associated with education reform. Nonetheless, school and university students in the MENA region still generally do poorly on standardised critical thinking tests (Amrous & Nejmaoui, 2016;McLellan, 2009), including in the Sultanate of Oman (Kumar & James, 2015;Mehta, Al-Mahrooqi, Denman, & Al-Aghbari, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative, participatory, experiential, engaging, and independent learning instructional strategies have fostered improved levels of critical thinking abilities among college students [23,24]. Further, the use of deliberative and reflective assessments has enhanced students' critical thinking skills and dispositions [25,26]. Embedding real-world illustrations and casebased teaching allows students to practice intended critical thinking skills [27].…”
Section: Instructional Methods Fostering Critical Thinkingmentioning
confidence: 99%